2023
DOI: 10.1088/1742-6596/2523/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Monofacial and Bifacial Photovoltaics Systems with Uniaxial Solar Tracking

Mohamed Humaid Bhayat,
Chockalingam Aravind Vaithilingam,
Kameswara Satya Prakash Oruganti
et al.

Abstract: The technology behind Bifacial Photovoltaic systems has existed for a long time but only recently gained popularity due to the increased surface area for the absorption of solar radiation by the rear-side of the bifacial Photovoltaic (PV) panel. The bifacial gain and output energy yield (kWh) is affected negatively by self-shading leading to non-uniformity in the absorbed irradiance. The purpose of this research is to simulate and investigate the effect of varying parameters including the elevation of a bifaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…In addition to modelling the PV module in the CAD software, the effect of indirect irradiation due to albedo from the ground/bottom surface was represented by a 5m × 5m surface located 0.8 m below the plane of the PV module with the centre of the plane and the PV module overlapping each other. This height was chosen based on the results of one of our previous studies [15] to obtain the maximum indirect irradiation on the back surface of the PV module. The surface area of the ground model was determined based on the minimum value at which the bifacial gain (BG) would not be affected/reduced due to the variation in area for a given panel footprint.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to modelling the PV module in the CAD software, the effect of indirect irradiation due to albedo from the ground/bottom surface was represented by a 5m × 5m surface located 0.8 m below the plane of the PV module with the centre of the plane and the PV module overlapping each other. This height was chosen based on the results of one of our previous studies [15] to obtain the maximum indirect irradiation on the back surface of the PV module. The surface area of the ground model was determined based on the minimum value at which the bifacial gain (BG) would not be affected/reduced due to the variation in area for a given panel footprint.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was done for the system pictured in figure 3. In addition to normal sunlight, the data showed that there was a big boost in capturing light that was reflected/scattered from the surroundings [15].…”
Section: Introductionmentioning
confidence: 99%